Pengaruh Persepsi Harga Dan Brand Image Terhadap Keputusan Pembelian Ulang Sabun Mandi Merek Nuvo (Studi Kasus di Desa Rawang Kota Pariaman) - Maharani Putri; Sri Mulyani (CV. ITTC INDONESIA, 2024)
This research is entitled The Influence of Price Perception and Brand Image on the Decision to Repurchase Nuvo Brand Bath Soap (Case Study in Rawang Village, Pariaman City) where research by many people has made bath soap a daily necessity. People with low economic conditions tend to use Nuvo soap as an alternative to meet their needs, but there are so many new brands available that this soap is less popular with consumers. This research uses primary data by distributing questionnaires to respondents and the data is processed using SPSS. Looking at the test results that have been carried out proves that partially the price perception and brand image variables have a significant influence on repurchase decisions, and simultaneously price perception and brand image have a significant influence on repurchase decisions.